2010
DOI: 10.1186/1472-6963-10-254
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Mask Airway for neonatal resuscitation in a developing country: evaluation of an educational intervention. Neonatal LMA: an educational intervention in DRC

Abstract: BackgroundStudies carried out in developing countries have indicated that training courses in newborn resuscitation are efficacious in teaching local birth attendants how to properly utilize simple resuscitation devices. The aim of this study was to assess the knowledge and expertise gained by physicians and midwifes who participated in a Neonatal Resuscitation Course and workshop organized in a Third World Country on the use of Laryngeal Mask Airway (LMA).MethodsA 28-item questionnaire, derived from the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…All participants (7 midwives and 21 physicians), expressed a high degree of approval with regard to neonatal resuscitation by LMA and defined it a sustainable and cost-effective procedure. 26 The present study, conducted in a middle resource setting after a short training of the staff, confirms these features. As the effectiveness and safety of the SLMA as well as the grade of satisfaction expressed by the staff were high, we believe that using LMA use for neonatal resuscitation might be easier than tracheal intubation, especially in settings where staffs are not familiar with tracheal intubation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All participants (7 midwives and 21 physicians), expressed a high degree of approval with regard to neonatal resuscitation by LMA and defined it a sustainable and cost-effective procedure. 26 The present study, conducted in a middle resource setting after a short training of the staff, confirms these features. As the effectiveness and safety of the SLMA as well as the grade of satisfaction expressed by the staff were high, we believe that using LMA use for neonatal resuscitation might be easier than tracheal intubation, especially in settings where staffs are not familiar with tracheal intubation.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it is important that our results are in agreement with a recent RCT showing that basic life support trained nurses were able to ventilate more efficiently with SLMA than with face mask or laryngeal tube suctiondisposable after 1 hour of introductory training. 26 The findings of our study are important for other units/settings in high as well low resource countries where neonatal resuscitation is more often performed by pediatricians, midwives, or nurses. In agreement with the study by Zhu et al, our results confirm that a short-term educational program on the LMA use is effective in the clinical practice.…”
Section: Discussionmentioning
confidence: 88%
“…Ten (22.2%) of the 45 studies reported a breakdown of scores according to cadre, 26,36,39,40,44,50,53,55,56,74 and 7 (70.0%) of these studies showed that birth attendants from lower cadres (eg, midwives) improved significantly more from pretraining to posttraining than those from higher cadres (eg, physicians). 26,40,42,50,53,56,74 In all 7 of these studies, significant differences in pretraining test performance between different cadres were diminished or completely eliminated upon retesting after training. Similarly, a study from HBB in Tanzania found that nurses outperformed health care providers of both higher and lower training levels on a standardized OSCE.…”
Section: Association Between Birth Attendant Characteristics and Acqumentioning
confidence: 99%
“…Over this period, the percentage of neonates receiving tracheal intubation at birth (34%) was significantly reduced compared with earlier figures (67%). In a recent study on training in use of LMA in a resource-limited country Zanardo (2010), it has been shown that both physicians and paramedics showed a significant improvement in their knowledge post training.…”
Section: Discussionmentioning
confidence: 99%